Remote Learning During the Global School Lockdown : Multi-Country Lessons - Barron Rodriguez, Maria; Cobo, Cristobal; Munoz-Najar, Alberto; Sanchez Ciarrusta, Inaki (World Bank, Washington, DC, 2021)
This study includes three main sections that have been organized in a chronological order within this report: the first one, “What can we learn from education emergency responses in low- and middle-income countries?” analyzes the emergency education responses to the COVID-19 pandemic of over 120 governments from April until May, 2020. The second section, “Is remote learning perceived as effective? An in-depth analysis across five countries” discusses the main national education responses deployed by Brazil, Kenya, Nigeria, Sierra Leone, and Peru, as well as the perceived effectiveness of these strategies conducted from May until August, 2020. The third section, “What works with remote and remedial strategies? an analysis across 13 countries” builds on key lessons learned during the analysis of the five multi-country experiences and presents global trends of remote learning implemented during school closures and the actions governments adopted to get ready for remedial learning, conducted from August until December 2020. The countries prioritized for the third section are IDA borrowing countries of which six are low-income countries.